1979
DOI: 10.1080/00222895.1979.10735181
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Task Specificity in Incidental Motor Learning

Abstract: The manipulation of the retention of a linear movement by means of different orienting tasks in an incidental learning paradigm was investigated. Subjects were presented with a target position followed by a different nontarget position on each of four presentation trials. After the presentation trials subjects were required to recall the target and nontarget positions. One group made verbal estimates of the distance between the target and nontarget positions, another group discriminated between the target and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The latter tend to focus on issues dealing with the capacity, coding, and forgetting characteristics which distinguish the various stores, while the former approach advocates the investigation of factors like the amount of attention paid to the stimulus and the compatibility of the stimulus with existing cognitive structures (Craik, 1973). While Craik and Lockhart's (1972) view of memory appears to have explanatory potential for the present data, as well as modest initial support from a recent study on motor memory in which an incidental-learning paradigm was used (Ho & Shea, 1979), it remains to be determined whether this framework or those advocating the existence of memory stores (see Baddeley, 1978, Eysenck, 1978, and Lockhart & Craik, 1978, for more recent discussions) will best explain the nature of memory for movement information. Until such time, it appears that conclusions as to the extent to which motor memory is a continuum or a dichotomy must be deferred.…”
mentioning
confidence: 58%
“…The latter tend to focus on issues dealing with the capacity, coding, and forgetting characteristics which distinguish the various stores, while the former approach advocates the investigation of factors like the amount of attention paid to the stimulus and the compatibility of the stimulus with existing cognitive structures (Craik, 1973). While Craik and Lockhart's (1972) view of memory appears to have explanatory potential for the present data, as well as modest initial support from a recent study on motor memory in which an incidental-learning paradigm was used (Ho & Shea, 1979), it remains to be determined whether this framework or those advocating the existence of memory stores (see Baddeley, 1978, Eysenck, 1978, and Lockhart & Craik, 1978, for more recent discussions) will best explain the nature of memory for movement information. Until such time, it appears that conclusions as to the extent to which motor memory is a continuum or a dichotomy must be deferred.…”
mentioning
confidence: 58%
“…Accordingly, the imposition of other meaningful organizations might facilitate procedural learning (Ho & Shea, 1979;Wright, 1991). On the other hand, the intrinsic spatial-temporal relationships might be the most meaningful organizer of procedural tasks.…”
Section: Meaningfulness and Learningmentioning
confidence: 99%
“…In the motor behavior research area, for instance, it has been suggested that PRESS ANY KEY TO CONTINUE multiple dependent measures should be reported to facilitate more direct comparisons of research (Battig, 1977;Ho & Shea, 1979). The software described in this paper is designed to permit a researcher to calculate all five error measures simultaneously, using a BASIC microcomputer program.…”
mentioning
confidence: 99%